Types of skeletal muscle fibre - Spurway, N. (Genetics and molecular biology of muscle adaptation, 2006)
CHAPTER CONTENTS Learning Objectives 62 Muscular Diversity 62 History 63 Histological and Histochemical Techniques 65 Classical Histology 65 Histochemistry 66 Metabolic Enzymes 66 Myosin ATPase - Basic Reactions 68 Myosin ATPase Reaction After Pre-treatments 69 Physiological Experiments 69 Chemical Quantification 71 Biochemistry 71 Quantitative Histochemistry 72 Electron Microscopy 73 Immunocytochemistry 74 Obtaining Specimens 76 The Three Main Fibre Types 77 Validity of the Fibre Type Concept 82 Quantitative Histochemistry 82 Cluster Analysis 82 Different Muscles 84 Different Species 85 Hybrid Fibres 86 The Size Principle 88 Match of Motor Unit Properties to Demand 89 What Determines Motor Unit Properties? 90 Unit Size 91 Nerve Cross-Union Experiments 91 Effects of Electrical Activation 93 Chemotrophism or Impulse-Dependent Mechanisms? 94 Other Influences on Fibre Type 95 Adaptation of Locomotor and Postural Muscles to Particular Functions 96 Differences Between Muscles 96 Sportspeople's Special Aptitudes 96 Effects of Training 99 Intracellular Systems 102 Two Puzzles 102 Independent Variation of the Several Systems 103 Significance of Non-Mammalian Situations for this Book 105 Factors Affecting Fibre Size 107 Twitches, Tetani and Shortening Velocity 108 The Variety of Myosins 110 Identification of Type 2X 110 2M 112 Others 112 Key Points 114 Further Reading 115 References 115